Diurnal Variation of Corneal Dendritic Cell Density. (2nd September 2022) - Alotaibi, Sultan; Ozkan, Jerome; Papas, Eric; Markoulli, Maria
Abstract: Purpose: To measure variation in corneal dendritic cell density, and percentage of mature to total dendritic cells, in healthy individuals during the sleep/wake cycle. Methods: Using in vivo confocal microscopy, images of the subbasal nerve plexus were captured from 19 healthy, noncontact lens wearing participants. The central cornea and inferior whorl were imaged three times (midday, before sleep, upon awakening). Dendritic cell counts from the images were categorized according to perceived maturity (immature vs mature). Dendritic cell density and percentage of mature to total cells were compared between time points. Result: The median and interquartile range (IQR) of total dendritic cell density in the central cornea was 32.0 (7.0–131.3) cells/mm 2 at midday, 37.1 (8.2–103.9) cells/mm 2 before sleep, and 19.5 (7.0–83.2) cells/mm 2 on awakening. Corresponding values for immature cells were 28.1 (5.8–112.5) cells/mm 2, 22.3 (7.4–84.0) cells/mm 2 and 18.0 (2.9–64.8) cells/mm 2, and for mature cells, 3.1 (0.0–6.6) cells/mm 2, 2.0 (0.8–16.8) cells/mm 2, and 1.6 (0.2–8.2) cells/mm 2 . At the inferior whorl, total dendritic cell density was 38.5 (18.4–84.5) cells/mm 2, 34.4 (9.4–82.3) cell/mm 2, and 32.3 (15.2–96.1) cells/mm 2 . Immature cell density was 32.8 (18.4–80.9) cells/mm 2, 34.4 (8.6–81.0) cells/mm 2, and 32.3 (12.6–78.5) cells/mm 2 . Mature cell density was 1.6 (0.0–6.3) cells/mm 2, 1.6 (0.0–3.1) cells/mm 2, and 1.8 (0.0–6.3) cells/mm 2 . There was no significant difference between time points for total cell density ( p  > 0.05), but the percentage of mature cells upon awakening was significantly greater, compared to midday, at the central cornea ( p  = 0.02). Conclusion: In healthy individuals, overall corneal dendritic cell density is reasonably constant during the sleep/wake cycle, but the relative number of mature cells tends to increase overnight.